K Means Cluster Analysis Risk Analysis in IOB - Sasikala, D; S.Vasantha, Dr; M. Sangeetha, Dr (International Journal of Engineering and Technology, 2018)
Purpose: Indian Banking industry has witnessed a vast change since the era of globalization, liberalization, increased competition, technological advancement and regulatory amendments. Different types of risks have a potentially negative effect on banking business. Risk identification, measurement and assessment, and its objective is to minimize negative effects risks can have on the financial result and capital of a bank constitutes risk management in bank. Objectives of the Study: The study aims to estimate the risk managementand risk bearing capabilities of IOB. Design/methodology/approach: The Bank IOB has been taken as sample unit to do research.The period considered for the studyis 5 years. The research uses secondary data. The data is collected from the financial statements for the period of analysis from 2013-2017 moneycontrol.com and the annual reports of the banks. Tools Used to Measure Risk: Ratio Analysis is exploited to compare the financial position with risk management of IOB.The K-means cluster analysis is used to segment the years with respect to different financial ratios. Scope and Limitations of the Study: Only sixteen ratios were taken for the measurement of risk. The performance of IOBÂ bank has been computed only for the period of 5 years i.e., 2013-2017. The study used the secondary data for analysis and interpretations.Â